Assessment of Pathogenicity Assay of Ascochyta rabiei Isolates Using Chickpea Differential Genotypes - Istanbuli, Tawffiq; Tawkaz, Sawsan; Moukahel, Abdulrahman; Kemal, Seid Ahmed; Hamwieh, Aladdin (Australian National Chickpea Ascochyta Blight, 2022)
Ascochyta blight caused by Ascochyta rabiei, is the most destructive disease in many chickpea growing countries. Many chickpea varieties were out of production due to increased virulence/aggressiveness of the pathogen in some countries. The aim of this study was to assess variation in pathogenicity of 25 A. rabiei collected in different years from Syria, Lebanon, Uzbekistan, and France. The pathogen phenotyping was done using five genotypes (ILC3279, ILC482, ICC3396, ICC12004, and Genesis090) under controlled conditions (humidity >85, temperature 18-20 °C, light/dark 18:6 h) at the International Center of Agricultural Research in the Dry Area (ICARDA), Terbol station, Lebanon. Five genotypes carrying different resistant genes have been used in this study, and a highly susceptible genotype (ILC263). was used as a control. A total of 25 sets of these genotypes, each genotype has two replications that have been planted and inoculated with the 25 A. rabiei isolates. The symptoms were measured two times using a 1–9 disease symptoms rating scale (RS) when the susceptible control was RS >6. The result showed high significant differences between genotypes (G) (P<0.001), and isolations (P<0.001). The average of resistance for the five genotypes was 3.5 compared to the susceptible check which scored ≥6. The results indicated 5 isolates were highly aggressive isolates Pathotype 4 & race 4 from Syria, Uz3-2 from Uzbekistan, and FR-2926 & FR-3248 from France). Further large-scale evaluation of these isolates on the AB differential set may help to identify a better understanding of the resistant genes available in chickpeas.